2010
DOI: 10.3393/jksc.2010.26.5.316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Delay in the Snap Freezing of Colorectal Cancer Tissues on the Quality of DNA and RNA

Abstract: PurposeThe success of basic molecular research using biospecimens strongly depends on the quality of the specimen. In this study, we evaluated the effects of delayed freezing time on the stability of DNA and RNA in fresh frozen tissue from patients with colorectal cancer.MethodsTissues were frozen at 10, 30, 60, and 90 minutes after extirpation of colorectal cancer in 20 cases. Absorbance ratio of 260 to 280 nm (A260/A280) and agarose gel electrophoresis were evaluated. In addition, the RNA integrity number (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 12 publications
4
26
0
Order By: Relevance
“…Overall, 93% of studies reported at least two diagnostic and two predictive measures of quality,12 17–24 26–30 with the majority of studies (53%) reporting at least six of the nine diagnostic and/or predictive quality measures 12 18 20–22 27–29. Moreover, of those, 25% of studies reported at least seven of the nine measures of interest 21 28…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 93% of studies reported at least two diagnostic and two predictive measures of quality,12 17–24 26–30 with the majority of studies (53%) reporting at least six of the nine diagnostic and/or predictive quality measures 12 18 20–22 27–29. Moreover, of those, 25% of studies reported at least seven of the nine measures of interest 21 28…”
Section: Resultsmentioning
confidence: 99%
“…This may explain the relatively low number of samples containing more than 60% tumor nuclei we obtained compared with previous studies. 18,19 Taking samples from a more central location in the tumor would likely have increased this value, but might also increase the number of samples with large necrosis. Although our FFPE and fresh frozen tissue came from the same biopsy, some differences between the two pieces could be present.…”
Section: Discussionmentioning
confidence: 97%
“…A more accurate image of the content in the fresh frozen pieces would likely be obtained if mirror-image slides were prepared from each end of the fresh frozen piece. 18,20 However, tissue morphology can be distorted during the liquid nitrogen snap freezing process.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that any delay in getting the sample from the living state to a preserved state (frozen, in formalin (FFPE) or RNAlater) will decrease the quality of the sample (Hong et al, 2010). There are other studies that indicate that there is at least a 16 hour window in which the sample collection and the QC metrics of BioAnalyzer assessment do not show any degradation (Micke et al, 2006).…”
Section: Sample Collectionmentioning
confidence: 99%